Fecal Microbiota Transplantation from Methionine-Restricted Diet Mouse Donors Improves Alzheimer’s Learning and Memory Abilities Through Short-Chain Fatty Acids - Run Yu; Haimeng Zhang; Rui Chen; Yangzhuo Lin; Jingxuan Xu; Ziyang Fang; Yuehang Ru; Chenhan Fan; Guoqing Wu (Foods)
Alzheimer’s disease (AD) is marked by impaired cognitive functions, particularly in learning and memory, owing to complex and diverse mechanisms. Methionine restriction (MR) has been found to exert a mitigating effect on brain oxidative stress to improve AD. However, the bidirectional crosstalk between the gut and brain through which MR enhances learning and memory in AD, as well as the effects of fecal microbiota transplantation (FMT) from MR mice on AD mice, remains underexplored. In this study, APP/PS1 double transgenic AD mice were used and an FMT experiment was conducted. 16S rRNA gene sequencing, targeted metabolomics, and microbial metabolite short-chain fatty acids (SCFAs) of feces samples were analyzed. The results showed that MR reversed the reduction in SCFAs induced by AD, and further activated the free fatty acid receptors, FFAR2 and FFAR3, as well as the transport protein MCT1, thereby signaling to the brain to mitigate inflammation and enhance the learning and memory capabilities. Furthermore, the FMT experiment from methionine-restricted diet mouse donors showed that mice receiving FMT ameliorated Alzheimer’s learning and memory ability through SCFAs. This study offers novel non-pharmaceutical intervention strategies for AD prevention.